Expression of outdoor and indoor spaces in Indonesian menggugat buildings from the aspect of the application of sustainable materials - Agung Prabowo Sulistiawan; Quiny Fazel Nafila; Julia Dwina Rachmawaty; Fikri Baihaqi; Seruni Shafa Nurbaya (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2023)
Cultural heritage buildings can be interpreted as witnesses to the journey of a country that can be found in every city throughout Indonesia. In line with this, the preservation of Cultural Heritage Buildings (BGCB) must meet technical requirements, preservation requirements, orderly operation of building buildings, and must be continuously maintained. One of the Cultural Heritage Buildings (BGCB) in Bandung City is the Indonesia Menggugat Building located on Jalan Perintis Kemerdekaan, No. 5, Babakan Ciamis, Sumur Bandung, Babakan Ciamis, Kec. Sumur Bandung, Bandung City. In this research, the method used is a qualitative method with primary data collection techniques (direct observation) and secondary data (references and theories). These two techniques, it is expected to produce a comprehensive understanding of the research topic. The variables of this research are focused on 3 variables, namely the style, color, and texture of the material. Field surveys and interviews were also conducted to support the analysis of the preservation of the Building of Cultural Heritage (BGCB) Gedung Indonesia Menggugat in Bandung. The analysis carried out refers to several parts of the outer space and inner space of the Indonesia Menggugat Building which uses a lot of old materials that are still maintained and reused. Some of these materials such as window openings use teak wood material which is finished with brown lacquer paint to have a natural impression and have good durability. The results of the study show that the effect produced by the use of sustainable materials in the Indonesia Menggugat Building can give the impression that the building feels natural under the use of color in the material. The Neo Classic concept is seen in the texture of materials that are organized and comfortable to look at. The roof, walls, and openings have a positive influence on the expression of the building's outer space when viewed from color, texture, and pattern. In the inner space, sustainable material elements dominate, creating an attractive and expressive impression. The research conclusion shows that the application of sustainable materials with an ecological approach to architecture in the Indonesia Menggugat Building has been applied quite well.